Synthesis process of environment-friendly halogen-free flame-retardant polyamide composite material

By surface modification of aluminum hypophosphate and synergistically used with melamine polyphosphate, the problem of poor environmental protection performance of existing flame-retardant polyamide composite materials is solved, and the environmental protection performance and mechanical properties of halogen-free flame-retardant polyamide composite materials are improved.

CN119570243AInactive Publication Date: 2025-03-07GUANGDONG TAISU NEW MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411631382.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing flame retardant polyamide composites have problems with poor environmental protection performance, especially halogen flame retardants will produce smoke and toxic gases during combustion, which are subject to environmental protection and market restrictions.

Method used

The surface modification of aluminum hypophosphate was performed by mechanical grinding method, combining aluminate coupling agent and rare earth aluminate coupling agent to form a mesh crosslinked macromolecular structure, improving the compatibility of aluminum hypophosphate in PA66 composite materials, and synergistically with melamine polyphosphate as a flame retardant, and increasing the use of long glass fibers to improve mechanical properties.

Benefits of technology

The environmental protection performance of halogen-free flame-retardant polyamide composite material is improved, and the thermal decomposition temperature of the composite material is reduced, which prompts it to quickly form carbon during combustion, improve the carbon layer structure, and maintain good mechanical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a synthesis process of an environment-friendly halogen-free flame-retardant polyamide composite material, and belongs to the technical field of halogen-free flame-retardant polyamide composites.The synthesis process comprises the steps that firstly, the surface of an aluminum hypophosphite material is modified through a mechanical grinding method; meanwhile, an aluminate coupling agent and a rare earth aluminate coupling agent are respectively matched to react to generate a reticular cross-linked macromolecular structure, so that the compatibility of aluminum hypophosphite in a PA66 composite material system is improved; then, the modified aluminum hypophosphite prepared in the previous step and melamine polyphosphate are subjected to a synergistic effect to jointly serve as a flame retardant; the long glass fiber is used for reinforcing and toughening to improve the mechanical property of the composite material; finally, the environment-friendly halogen-free flame-retardant polyamide composite material is obtained. The technical problem of how to improve the environmental protection performance of the flame-retardant polyamide composite material is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of halogen-free flame-retardant polyamide composite materials, and in particular to a synthesis process of an environmentally friendly halogen-free flame-retardant polyamide composite material. Background Art

[0002] Polyamide, or PA for short, is a heterochain polymer with an amide group in the main chain. The main varieties are PA6 and PA66, which account for more than 90% of the total output of polyamide. With its outstanding characteristics of strong tensile strength, good abrasion resistance, strong corrosion resistance and fatigue resistance, polyamide materials are widely used in many industrial fields such as chemical fiber textiles, transportation, electronic appliances and construction, and are an important part of today's new materials industry.

[0003] However, polyamide itself has a low limiting oxygen index and is a flammable material. It is easily ignited and has a molten dripping phenomenon, which in turn produces secondary damage, which to a certain extent reduces the application range of polyamide. Therefore, the research on flame retardant modified polyamide is a development focus.

[0004] At present, there are two commonly used methods for flame-retardant modified polyamide. One is reactive flame retardancy, that is, in the polymerization process, the structure of the base material polyamide polymer is changed by chemical reaction, and functional groups with flame retardant activity are added therein. However, the actual experimental operation is complicated, resulting in increased production costs; therefore, it is rarely used in actual industrial production projects; the other is additive flame retardancy, in which a single or compound flame retardant is mixed, melted, and extruded with a polyamide base material, so that it can exhibit higher fire resistance in industry. This method is simple to operate and low in cost, and is the most commonly used method in the current engineering application field; however, the uniform dispersion of the flame retardant in the polyamide material cannot be accurately controlled, which has some uncertain factors affecting the overall performance of the material.

[0005] Based on this, Chinese patent CN101374897B discloses a flame retardant polyamide composition, the composition includes a thermoplastic polyamide, a flame retardant system and a phosphite stabilizer, the flame retardant system includes a halogenated flame retardant compound and a flame retardant synergist, and the polyamide composition is substantially free of antimony compounds. Among them, the known composition includes a thermoplastic polyamide, more specifically, a semi-crystalline polyamide with a melting point of 280-340°C. The known composition includes a flame retardant containing 50-70% by weight of bromine as a halogenated flame retardant compound. The known composition includes 1 to 10% by weight of an antimony compound and 0.1% by weight of zinc borate as a flame retardant synergist. The technical solution disclosed in this patent can make the polyamide composition have a flame retardant effect.

[0006] However, the flame retardant polyamide composition disclosed above still has the technical problem of poor environmental performance. Specifically, with the promulgation of the EU "RoHS" and "REACH" directives, halogen flame retardants are gradually being eliminated by market and environmental protection standards because they produce smoke and a large amount of toxic and harmful gases during combustion, which not only pollutes the environment but also endangers the lives of the public. Therefore, more and more industries, departments, and industrial fields have begun to restrict or prohibit the use of flame retardants containing halogen elements. Green halogen-free flame retardant polyamide is the development trend of the current flame retardant industry that focuses on environmental friendliness and ecological safety. Summary of the invention

[0007] Based on this, it is necessary to provide a synthesis process of an environmentally friendly halogen-free flame retardant polyamide composite material in order to solve the technical problem of how to improve the environmental performance of the flame retardant polyamide composite material.

[0008] A synthesis process of an environmentally friendly halogen-free flame-retardant polyamide composite material comprises the following steps: S1: preparing the modification process materials according to the preset ratio: aluminum hypophosphite, aluminate coupling agent and rare earth aluminate coupling agent; S2: using a mechanical grinding method to perform surface modification on the pre-prepared pre-treatment material to obtain modified aluminum hypophosphite; S3: Prepare the extrusion materials according to the preset ratio: modified aluminum hypophosphite, PA66 pellets, antioxidant 1098, long glass fiber, TAF and melamine polyphosphate; S4: drying the modified aluminum hypophosphite and PA66 pellets in a vacuum drying oven at 80° C. for 4 hours to remove moisture from the materials; S5: preheat the oil temperature of the high-speed mixer to 80°C; first, uniformly mix the PA66 pellets and the antioxidant 1098 for 1 to 2 minutes according to the ratio of the materials in step S4; then pour in the melamine polyphosphate and the modified aluminum hypophosphite and mix at high speed for 3 to 4 minutes; finally, pour in the long glass fiber and TAF and mix for 2 to 3 minutes before discharging; the moisture content of the material at this time is less than 0.5% in order to prevent the particles from becoming hollow and foamed during the twin-screw extrusion process; S6: placing the mixed materials in a twin-screw extruder for extrusion and granulation; the temperature of the twin-screw extruder is set to: T1=200℃, T2=210℃, T3=220℃, T4=230℃ and T5=240℃; the head temperature is set to 230℃; the main engine screw speed is: 170n / min, the feed speed is 25n / min, and the main engine current is controlled at: 32.4 to 35.6A; the extruded melt is water-cooled and granulated by a pelletizer; S8: The prepared pellets are placed in a vacuum drying oven and dried at 80° C. for 8 hours to obtain an environmentally friendly halogen-free flame-retardant polyamide composite material.

[0009] Specifically, in step S2, the surface of the pre-prepared pre-treatment material is modified by mechanical grinding to obtain modified aluminum hypophosphite, and the specific process includes the following steps: S21: drying the aluminum hypophosphite in a vacuum drying oven at 80° C. for 8 hours to remove moisture from the material; S22: putting aluminum hypophosphite and rare earth aluminate coupling agent in a preset ratio into a planetary ball mill equipped with grinding balls with preset weights, and setting the parameters of the ball milling to: intermittent unidirectional operation for 60 minutes, stop for 5 minutes, and repeat this operation for 5 times; S23: continuing to add a preset ratio of aluminate coupling agent into the planetary ball mill, the parameters of the ball mill are set to: intermittent bidirectional operation for 30 minutes, stop for 10 minutes, and repeat this operation for 3 times; S24: Take out the modified aluminum hypophosphite from the planetary ball mill for later use.

[0010] Specifically, in step S22, the weight of the grinding balls is set to: the weight of the grinding balls ≥ (the weight of the aluminum hypophosphite + the weight of the rare earth aluminate coupling agent) * 3.

[0011] Specifically, the parameter change setting of the ball mill is: intermittent bidirectional operation for 15 minutes, stop for 5 minutes, and cycle this operation for 6 times.

[0012] Specifically, in step S1, the ratio of the pre-treatment material is: 50 parts of aluminum hypophosphite, 1 part of aluminate coupling agent and 1 part of rare earth aluminate coupling agent, by mass.

[0013] Specifically, in step S1, the ratio of the pre-treatment material is: 49 parts of aluminum hypophosphite, 0.5 parts of aluminate coupling agent and 0.5 parts of rare earth aluminate coupling agent, by weight.

[0014] Specifically, in step S1, the ratio of the pre-treatment material is: 48 parts of aluminum hypophosphite, 1.5 parts of aluminate coupling agent and 0.5 parts of rare earth aluminate coupling agent, by weight.

[0015] Specifically, in step S3, the ratio of the extruded materials is, by mass, 12 parts of modified aluminum hypophosphite, 48 parts of PA66 pellets, 0.1 parts of antioxidant 1098, 30 parts of long glass fiber, 0.9 parts of TAF and 9 parts of melamine polyphosphate.

[0016] Specifically, in step S3, the ratio of the extruded materials is, by mass, 11 parts of modified aluminum hypophosphite, 49 parts of PA66 pellets, 0.1 parts of antioxidant 1098, 30 parts of long glass fiber, 0.9 parts of TAF and 9 parts of melamine polyphosphate.

[0017] Specifically, in step S3, the ratio of the extruded materials is, by mass, 10 parts of modified aluminum hypophosphite, 50 parts of PA66 pellets, 0.1 parts of antioxidant 1098, 30 parts of long glass fiber, 0.9 parts of TAF and 9 parts of melamine polyphosphate.

[0018] In summary, the synthesis process of the environmentally friendly halogen-free flame-retardant polyamide composite material of the present invention first modifies the surface of the aluminum hypophosphite material by mechanical grinding; at the same time, respectively cooperate with an aluminate coupling agent and a rare earth aluminate coupling agent to react to generate a network cross-linked macromolecular structure to improve the compatibility of the aluminum hypophosphite in the PA66 composite material system; then, the modified aluminum hypophosphite prepared in the above steps and melamine polyphosphate are synergistically used as flame retardants; and then reinforced and toughened with long glass fibers to improve the mechanical properties of the composite material; finally, an environmentally friendly halogen-free flame-retardant polyamide composite material is obtained. The addition of modified aluminum hypophosphite and melamine polyphosphate enables the composite material to not only reflect environmental performance, but also reduce the thermal decomposition temperature of the composite material, prompting the composite material to quickly form carbon when burning, effectively improving the structure of the carbon layer, and at the same time, allowing the flame-retardant PA66 composite material to maintain good mechanical properties. Therefore, the synthesis process of the environmentally friendly halogen-free flame-retardant polyamide composite material of the present invention solves the technical problem of how to improve the environmental performance of flame-retardant polyamide composite materials. DETAILED DESCRIPTION

[0019] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific implementation mode of the present invention is described in detail below in conjunction with embodiments. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.

[0020] Specifically, the synthesis process of the environmentally friendly halogen-free flame-retardant polyamide composite material of the present invention comprises the following steps: S1: preparing the modification process materials according to the preset ratio: aluminum hypophosphite, aluminate coupling agent and rare earth aluminate coupling agent; S2: using a mechanical grinding method to perform surface modification on the pre-prepared pre-treatment material to obtain modified aluminum hypophosphite; S3: Prepare the extrusion materials according to the preset ratio: modified aluminum hypophosphite, PA66 pellets, antioxidant 1098, long glass fiber, TAF and melamine polyphosphate; S4: drying the modified aluminum hypophosphite and PA66 pellets in a vacuum drying oven at 80° C. for 4 hours to remove moisture from the materials; S5: preheat the oil temperature of the high-speed mixer to 80°C; first, uniformly mix the PA66 pellets and the antioxidant 1098 for 1 to 2 minutes according to the ratio of the materials in step S4; then pour in the melamine polyphosphate and the modified aluminum hypophosphite and mix at high speed for 3 to 4 minutes; finally, pour in the long glass fiber and TAF and mix for 2 to 3 minutes before discharging; the moisture content of the material at this time is less than 0.5% in order to prevent the particles from becoming hollow and foamed during the twin-screw extrusion process; S6: placing the mixed materials in a twin-screw extruder for extrusion and granulation; the temperature of the twin-screw extruder is set to: T1=200℃, T2=210℃, T3=220℃, T4=230℃ and T5=240℃; the head temperature is set to 230℃; the main engine screw speed is: 170n / min, the feed speed is 25n / min, and the main engine current is controlled at: 32.4 to 35.6A; the extruded melt is water-cooled and granulated by a pelletizer; S8: The prepared pellets are placed in a vacuum drying oven and dried at 80° C. for 8 hours to obtain an environmentally friendly halogen-free flame-retardant polyamide composite material.

[0021] Specifically, in the aforementioned step S2, the surface of the pre-prepared pre-treatment material is modified by mechanical grinding to obtain the modified aluminum hypophosphite, and the specific process includes the following steps: S21: drying the aluminum hypophosphite in a vacuum drying oven at 80° C. for 8 hours to remove moisture from the material; S22: putting aluminum hypophosphite and rare earth aluminate coupling agent in a preset ratio into a planetary ball mill equipped with grinding balls with preset weights, and setting the parameters of the ball milling to: intermittent unidirectional operation for 60 minutes, stop for 5 minutes, and repeat this operation for 5 times; S23: continuing to add a preset ratio of aluminate coupling agent into the planetary ball mill, the parameters of the ball mill are set to: intermittent bidirectional operation for 30 minutes, stop for 10 minutes, and repeat this operation for 3 times; S24: Take out the modified aluminum hypophosphite from the planetary ball mill for later use.

[0022] Specifically, in the aforementioned step S22, the weight of the grinding ball is set as follows: the weight of the grinding ball ≥ (the weight of aluminum hypophosphite + the weight of the rare earth aluminate coupling agent) * 3; for example, the weight of the aluminum hypophosphite input is 50g, and the weight of the rare earth aluminate coupling agent is 1g; then the weight of the grinding ball should be at least 153g.

[0023] More specifically, in the aforementioned step S23, the parameters of the ball mill are changed to: intermittent bidirectional operation for 15 minutes, stop for 5 minutes, and repeat the operation 6 times in this regular cycle. In this way, the particle size of the material can be made finer.

[0024] Specifically, phosphorus-based flame retardants, as the core additive of halogen-free flame retardants, are considered to be a promising method due to their high flame retardant efficiency. Phosphorus-based flame retardants are divided into organic phosphorus-based and inorganic flame retardants. Compared with organic phosphorus-based flame retardants, inorganic phosphorus-based flame retardants have the advantages of good thermal stability, low cost and environmental friendliness, and are more popular. Aluminum hypophosphite, as a typical inorganic phosphorus-based flame retardant, has the characteristics of environmental friendliness and high efficiency, but aluminum hypophosphite has poor water resistance and strong hygroscopicity, which is not conducive to storage, transportation and use.

[0025] The synthesis process of the environmentally friendly halogen-free flame-retardant polyamide composite material of the present invention proposes a technical means for surface modification of aluminum hypophosphite using an aluminate coupling agent and a rare earth aluminate coupling agent, wherein the aluminate coupling agent, as an important surfactant, has high surface reactivity and is environmentally friendly. Its structural formula is: (RO)xAl(OCR')m·Dn, and there are two different functional groups in the aluminate coupling agent -(RO)x represents a hydrophilic group, -(OCR)m represents a hydrophobic group, and Dn represents a coordination group. The hydrophilic group can react chemically with the polar group on the surface of the inorganic flame retardant to reduce the surface energy of the aluminum hypophosphite. The prepared superhydrophobic material has good environmental stability. Furthermore, the rare earth aluminate coupling agent, as a surfactant, can improve the interfacial properties of the organic resin and the inorganic flame retardant, so as to play a synergistic modification effect in the surface modification process of the aluminum hypophosphite.

[0026] In addition, melamine polyphosphate is an intumescent phosphorus-nitrogen flame retardant that integrates acid source and gas source, and has the characteristics of high thermal decomposition temperature, good compatibility with base materials, and high flame retardant efficiency. As one of the research hotspots of flame retardants in recent years, phosphorus-nitrogen flame retardants can also generate dense carbon layers when phosphorus-nitrogen works synergistically, and have excellent flame retardant properties. It is a kind of green flame retardant with good flame retardant effect. Due to the synergistic effect between phosphorus and nitrogen, it is widely used in engineering plastic materials such as polyamide and polycarbonate with oxygen-containing groups in the molecular chain as the carbon source for intumescent foaming flame retardant. Thermal decomposition will produce a large amount of flame-retardant gas, which will expand the carbon layer and form a dense and porous carbon layer, which effectively insulates heat and oxygen, can effectively prevent dripping, and stop the fire from further expanding, so as to achieve the purpose of high-efficiency flame retardancy; moreover, there is a good synergistic flame retardant effect between MPP and other flame retardants.

[0027] Specifically, for the aforementioned step S1, the specific proportions of the three pre-treatment materials are as follows, calculated by weight: Pre-treatment material example 1: 50 parts of aluminum hypophosphite, 1 part of aluminate coupling agent and 1 part of rare earth aluminate coupling agent.

[0028] Pre-treatment material example 2: 49 parts of aluminum hypophosphite, 0.5 parts of aluminate coupling agent and 0.5 parts of rare earth aluminate coupling agent.

[0029] Pre-treatment material example 3: 48 parts of aluminum hypophosphite, 1.5 parts of aluminate coupling agent and 0.5 parts of rare earth aluminate coupling agent.

[0030] The experimental methods for the hydrophobicity of modified aluminum hypophosphite are as follows: Hydrophobicity test: The water contact angle of the flame retardant is characterized by using a JY-82 static water contact angle meter. Hydrophobicity test of flame retardant polyamide composites: First, 100 grams of aluminum hypophosphite and modified aluminum hypophosphite are placed in the mold of a tablet press, and then pressed into sheets under a certain pressure using a tablet press. Second, the static water contact angle of the sample is tested using a JY-82 water contact angle tester.

[0031] Using the aforementioned hydrophobicity test method, it can be seen that the water contact angle of aluminum hypophosphite is only 9.78°, indicating that aluminum hypophosphite has good hydrophilicity. The water contact angles of the modified aluminum hypophosphite prepared by pre-treatment material examples 1-3 have changed greatly, and are all greater than 90°. Specifically: The water contact angle of the pre-treated material Example 1 is: 119.26°; The water contact angle of the pre-treated material Example 2 is: 99.21°; The water contact angle of the pre-treated material in Example 3 is 108.92°.

[0032] It can be seen that the modification process has caused a qualitative change in the surface properties of aluminum hypophosphite, a complete transformation from hydrophilicity to hydrophobicity.

[0033] Furthermore, in the aforementioned step S3, the ratio of different extrusion materials is as follows, in parts by mass: Comparative Example: PA66, 100 parts.

[0034] Example 11: 12 parts of modified aluminum hypophosphite prepared from the pre-treated material Example 1, 48 parts of PA66 pellets, 0.1 parts of antioxidant 1098, 30 parts of long glass fiber, 0.9 parts of TAF and 9 parts of melamine polyphosphate; Example 12: 11 parts of modified aluminum hypophosphite prepared from the pre-treated material of Example 1, 49 parts of PA66 pellets, 0.1 parts of antioxidant 1098, 30 parts of long glass fiber, 0.9 parts of TAF and 9 parts of melamine polyphosphate; Example 13: 10 parts of modified aluminum hypophosphite prepared from the pre-treated material Example 1, 50 parts of PA66 pellets, 0.1 parts of antioxidant 1098, 30 parts of long glass fibers, 0.9 parts of TAF and 9 parts of melamine polyphosphate.

[0035] Further, each of the embodiments 11-13 can be evaluated by evaluating its LOI index and vertical burning test (UL-94), and the specific experimental results are shown in the following Table 1: Table 1: Flame retardant properties of PA6 composite materials with modified aluminum hypophosphite synergistic system

[0036] It can be seen from the flame retardant test results in Table 1 above that in different embodiment ratios, the synthesis process of the environmentally friendly halogen-free flame retardant polyamide composite material of the present invention can obtain a polyamide composite material with excellent flame retardant performance.

[0037] In summary, the synthesis process of the environmentally friendly halogen-free flame-retardant polyamide composite material of the present invention first modifies the surface of the aluminum hypophosphite material by mechanical grinding; at the same time, respectively cooperate with an aluminate coupling agent and a rare earth aluminate coupling agent to react to generate a network cross-linked macromolecular structure to improve the compatibility of the aluminum hypophosphite in the PA66 composite material system; then, the modified aluminum hypophosphite prepared in the above steps and melamine polyphosphate are synergistically used as flame retardants; and then reinforced and toughened with long glass fibers to improve the mechanical properties of the composite material; finally, an environmentally friendly halogen-free flame-retardant polyamide composite material is obtained. The addition of modified aluminum hypophosphite and melamine polyphosphate enables the composite material to not only reflect environmental performance, but also reduce the thermal decomposition temperature of the composite material, prompting the composite material to quickly form carbon when burning, effectively improving the structure of the carbon layer, and at the same time, allowing the flame-retardant PA66 composite material to maintain good mechanical properties. Therefore, the synthesis process of the environmentally friendly halogen-free flame-retardant polyamide composite material of the present invention solves the technical problem of how to improve the environmental performance of flame-retardant polyamide composite materials.

[0038] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0039] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A synthesis process of an environmentally friendly halogen-free flame-retardant polyamide composite material, characterized in that: It includes the following steps: S1: preparing the modification process materials according to the preset ratio: aluminum hypophosphite, aluminate coupling agent and rare earth aluminate coupling agent; S2: using a mechanical grinding method to perform surface modification on the pre-prepared pre-treatment material to obtain modified aluminum hypophosphite; S3: Prepare the extrusion materials according to the preset ratio: modified aluminum hypophosphite, PA66 pellets, antioxidant 1098, long glass fiber, TAF and melamine polyphosphate; S4: drying the modified aluminum hypophosphite and PA66 pellets in a vacuum drying oven at 80° C. for 4 hours to remove moisture from the materials; S5: preheat the oil temperature of the high-speed mixer to 80°C; first, uniformly mix the PA66 pellets and the antioxidant 1098 for 1 to 2 minutes according to the ratio of the materials in step S4; then pour in the melamine polyphosphate and the modified aluminum hypophosphite and mix at high speed for 3 to 4 minutes; finally, pour in the long glass fiber and TAF and mix for 2 to 3 minutes before discharging; the moisture content of the material at this time is less than 0.5% in order to prevent the particles from becoming hollow and foamed during the twin-screw extrusion process; S6: placing the mixed materials in a twin-screw extruder for extrusion and granulation; the temperature of the twin-screw extruder is set to: T1=200℃, T2=210℃, T3=220℃, T4=230℃ and T5=240℃; the head temperature is set to 230℃; the main engine screw speed is: 170n / min, the feed speed is 25n / min, and the main engine current is controlled at: 32.4 to 35.6A; the extruded melt is water-cooled and granulated by a pelletizer; S8: The prepared pellets are placed in a vacuum drying oven and dried at 80° C. for 8 hours to obtain an environmentally friendly halogen-free flame-retardant polyamide composite material.

2. The synthesis process of the environmentally friendly halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: In step S2, the surface of the prepared pre-treated material is modified by mechanical grinding to obtain modified aluminum hypophosphite. The specific process includes the following steps: S21: drying the aluminum hypophosphite in a vacuum drying oven at 80° C. for 8 hours to remove moisture from the material; S22: putting aluminum hypophosphite and rare earth aluminate coupling agent in a preset ratio into a planetary ball mill equipped with grinding balls with preset weights, and setting the parameters of the ball milling to: intermittent unidirectional operation for 60 minutes, stop for 5 minutes, and repeat this operation for 5 times; S23: continuing to add a preset ratio of aluminate coupling agent into the planetary ball mill, the parameters of the ball mill are set to: intermittent bidirectional operation for 30 minutes, stop for 10 minutes, and repeat this operation for 3 times; S24: Take out the modified aluminum hypophosphite from the planetary ball mill for later use.

3. The synthesis process of the environmentally friendly halogen-free flame-retardant polyamide composite material according to claim 2, characterized in that: In step S22, the weight of the grinding balls is set to: the weight of the grinding balls ≥ (the weight of the aluminum hypophosphite + the weight of the rare earth aluminate coupling agent) * 3.

4. The synthesis process of the environmentally friendly halogen-free flame-retardant polyamide composite material according to claim 2, characterized in that: The parameters of the ball mill were changed to: intermittent bidirectional operation for 15 minutes, stop for 5 minutes, and repeat this operation 6 times.

5. The synthesis process of the environmentally friendly halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: In step S1, the ratio of the pre-treatment material is: 50 parts of aluminum hypophosphite, 1 part of aluminate coupling agent and 1 part of rare earth aluminate coupling agent, by mass.

6. The synthesis process of the environmentally friendly halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: In step S1, the ratio of the pre-treatment material is: 49 parts of aluminum hypophosphite, 0.5 parts of aluminate coupling agent and 0.5 parts of rare earth aluminate coupling agent, by mass.

7. The synthesis process of the environmentally friendly halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: In step S1, the ratio of the pre-treatment material is: 48 parts of aluminum hypophosphite, 1.5 parts of aluminate coupling agent and 0.5 parts of rare earth aluminate coupling agent, calculated by weight.

8. The synthesis process of the environmentally friendly halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: In step S3, the ratio of the extruded materials is as follows, by mass: 12 parts of modified aluminum hypophosphite, 48 parts of PA66 pellets, 0.1 parts of antioxidant 1098, 30 parts of long glass fiber, 0.9 parts of TAF and 9 parts of melamine polyphosphate.

9. The synthesis process of the environmentally friendly halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: In step S3, the ratio of the extruded materials is as follows, by mass: modified aluminum hypophosphite, 11 parts, PA66 pellets, 49 parts, antioxidant 1098, 0.1 parts, long glass fiber, 30 parts, TAF, 0.9 parts, and melamine polyphosphate, 9 parts.

10. The synthesis process of the environmentally friendly halogen-free flame-retardant polyamide composite material according to claim 1, characterized in that: In step S3, the ratio of the extruded materials is as follows, by mass: 10 parts of modified aluminum hypophosphite, 50 parts of PA66 pellets, 0.1 parts of antioxidant 1098, 30 parts of long glass fiber, 0.9 parts of TAF and 9 parts of melamine polyphosphate.

Citation Information

Patent Citations

  • Flame retardant polyamide molding composition

    CN101374897B

  • Low-cost high-strength high-heat-resistance halogen-free flame-retardant PA66 composition and preparation method thereof

    CN109265992A

Cited By

  • Method for preparing phosphorane through pyrolysis of sodium hypophosphite based on raw material pretreatment

    CN120793858A